Kaarina Kailo, Sauna Culture, Sweat and Spirituality: On the architectonics and cosmology of sacred space - Bartlett, Elizabeth Ann (Matrix, 2026)
Elizabeth Bartlett offers a review of Kaarina Kailo's book Sauna Culture, Sweat and Spirituality: On the architectonics and cosmology of sacred space (Springer, 2025).